PERSPEKTIF KONDISI KESEHATAN KEUANGAN DAN KOMPLEKSITAS AUDIT DI PERUSAHAAN SARANA DAN PRASARANA DI BURSA EFEK INDONESIA TAHUN 2023-2025 - Totok Susilo Pamuji Nugroho; Chania Aulia (Riset Manajemen dan Akuntansi, 2026)
The purpose of this study is to examine how audit report lag in infrastructure sector companies listed on the Indonesia Stock Exchange between 2023 and 2025 is affected by financial health and audit complexity. The Fixed Effects model and panel data regression are two quantitative methods used in this study. Purposive sampling was used to obtain the sample, which included 90 observations in total. The study's independent variables are audit complexity, which is represented by the number of subsidiaries, and financial health, which is assessed using the Altman Z-Score. The dependent variable is audit report lag. Firm size is also employed as a control variable. According to the study's findings, audit report lag is significantly impacted negatively by financial health; that is, the better a company's financial situation, the quicker the audit is finished. On the other hand, audit report lag is significantly positively impacted by audit complexity, meaning that the length of the audit process increases with the complexity of a company's structure. Additionally, it was discovered that audit report lag was positively impacted by company size. This study offers the most recent empirical contribution to comprehending the dynamics of audit report lag in Indonesia's infrastructure sector and supports agency theory and signaling theory. It is anticipated that the findings of this study will assist businesses, auditors, and regulators in increasing the effectiveness and promptness of financial reporting.